Malaysia in the era of globalization - M. Bakri Musa (Mohammad Bakri Musa) (Writers Club Press, 2002)
Bakri Musa makes a persuasive argument for Malaysia to embrace globalization with conviction. It is the ticket to her Vision 2020 aspirations. Malaysia was well on her way to join the global mainstream when the 1997 economic crisis interrupted that trajectory. It is now time, the writer passionately pleads, to return to that path. Yes there are sandbars and reefs, together with the inevitable storms and swells in the ocean of globalization. This calls for skillful navigators and sailors ready to trim the sails and batten the hatches. The alternative would be to remain in port, not an attractive option. The writer offers specific prescriptions on how best to meet those challenges, from enhanced health care to superior education system, and by exposing Malaysians to greater competition. As Islam is a pervasive influence in Malaysia, the writer calls for an enlightened interpretation of the faith, one more in tune with its ideals of tolerance for diversity, reverence for learning, and a passion for trade. The writer draws lessons from as far away as Argentina and as far back as the ancient Muslims, and from sociology to biology. The perspectives offered here are refreshing departures from the wisdom currently emanating from Kuala Lumpur.